Implemetasi Pengaturan Pemberian Bantuan Sosial dalam Era Pandemi COVID-19 di Desa Adat Kuta - Ni Komang Ayu Febriyanti; I Wayan Wesna Astara; I Wayan Arthanaya (Jurnal Preferensi Hukum, 2021)
Public welfare is an effort made by the government which aims to improve the welfare of the community through social services and has a broad scope. The outbreak of the covid-19 virus in Indonesia resulted in the central government issuing policies on efforts to prevent the spread of the covid-19 virus which must be implemented by local governments. The purpose of this research is to reveal the arrangement of local government assistance funds in order to tackle covid-19 in the Kuta Traditional Village and the implementation of the provision of social assistance funds distributed to the community in the context of the Covid-19 pandemic. The method used is empirical legal research with a sociological approach. Sources of legal materials are primary, secondary and tertiary which are obtained directly through field research. The legal materials obtained then analyzed using qualitative descriptive techniques. The results of this research concluded that Kuta Traditional Village is not qualified in providing assistance considering that what was seen was the aspect of equality of indigenous peoples and agencies and the need for an organization and an implementation system so that the provision of social assistance can proceed well.